2017
DOI: 10.1021/acs.jpcc.7b04833
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Gas Adsorption onto ZIF-8 Using Terahertz Waves

Abstract: The adsorption behavior of energy-related gases onto ZIF-8 was investigated using terahertz waves. Comparison of the terahertz transmission spectra of ZIF-8 before and after exposure to the gases revealed that the 2 THz vibrational mode was involved in the gate-opening motion of organic linker molecules. The adsorption properties of each gas were detailed by monitoring the intensities of the 2 THz absorption peak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…2.0 THz (infrared active), has been controversial. 9,29 While a later study has claimed the spectral assignment by Tan et al 29 to be the correct one, 30 the results of the present study clearly…”
Section: Spectroscopic Fingerprint Of Mechanical Softening On Compressupporting
confidence: 56%
“…2.0 THz (infrared active), has been controversial. 9,29 While a later study has claimed the spectral assignment by Tan et al 29 to be the correct one, 30 the results of the present study clearly…”
Section: Spectroscopic Fingerprint Of Mechanical Softening On Compressupporting
confidence: 56%
“…[7][8][9][10] On the other hand, the complex and largeamplitude motions occurring at terahertz frequencies have recently been related to a wide-variety of bulk phenomena, for example phase transformations, 11,12 mechanical responses, 5,13,14 electron-phonon coupling, 15,16 and gas-capture in porous mate-rials. 17,18 Unfortunately, the factors that make terahertz spectroscopy a valuable analytical technique simultaneously lead to one of its biggest challenges -the interpretation of experimental results. Unlike mid-infrared (mid-IR) methods, such as Fourier transform infrared spectroscopy (FTIR) and mid-IR Raman scattering, there do not exist any functional-group specific transitions at terahertz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency (terahertz) vibrational dynamics have been shown to be one of the major factors that dictate the properties of condensed phase materials, ranging from thermodynamic to mechanical phenomena [1,2]. Additionally, a number of recent investigations have suggested that terahertz motions, which often involve large amplitude displacements of entire molecules, play a vital role in the proper functioning of materials [3][4][5][6][7][8]. However, the dependence of the low-frequency vibrations on both the intramolecular and intermolecular potential energy hypersurfaces leads to unique spectral fingerprints, which cannot be interpreted without additional analysis [9].…”
mentioning
confidence: 99%